Strategy to Improve Employee Performance of the Directorate of Human Resources and General Affairs of the Public Broadcasting Corporation of Radio Republik Indonesia (RRI) - Ferda Firmansyah; Asropi Asropi; Hamka Hamka (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to determine the background of employee performance within the Directorate of Human Resources and General Affairs of LPP RRI which is not optimal, and to find out strategies to improve employee performance within the Directorate of Human Resources and General Affairs of LPP RRI. The research method used in the research is descriptive research method with qualitative approach. The results showed several factors affecting employee performance at the Directorate of Human Resources and General Affairs of LPP RRI. Among them, the lack of open appreciation of employees can reduce motivation and job satisfaction. The level of internal coordination that needs to be improved also has an impact on efficiency and collaboration between employees. A poorly structured recognition and reward system can reduce morale, while periodic evaluations may not be optimal in maintaining and increasing employee motivation. Work design involving inclusive attitudes, promotion of tolerance, and administrative skills need to be improved to create a positive and efficient work environment. Factors such as interpersonal relationships, communication, compensation, supervision, work facilities, employee loyalty, and work discipline also affect performance and need attention in order to improve overall performance. The strategy to improve employee performance at the Directorate of Human Resources and General Affairs of LPP RRI focuses on three main aspects, namely Motivation, Traits, and Self-Concept. In the Motivation aspect, measures such as internal motivation development, structured recognition and rewards, and flexible HR policies are implemented to create a supportive and motivating environment for employees. In the Traits aspect, improved employee management, inspirational motivation, and employee development through continuing education programs are the focus to improve organizational efficiency and employee skills. While in the Self-Concept aspect, physical, emotional, intellectual, social, and spiritual improvements are made through various programs such as fitness, interpersonal training, and professional development. Through the implementation of this strategy, the Directorate of Human Resources and General Affairs of LPP RRI is expected to create a dynamic work environment, support holistic growth of employees, and ultimately improve overall performance.